COGNITIVE-DISCURSIVE FUNCTIONS OF ANGLO-AMERICAN PROVERBS - Konstantinova, Anna (Proverbium - Yearbook, 2017)
This article explores the role Anglo-American paremias (or proverbs), both standard and modified, play in the processes of cognition and communication. I argue that their cognitive nature as precedent utterances accounts for their ubiquity and their significant conceptual power. Indisputably, paremias possess certain rhetorical value but this “artful” dimension of the use of proverbs is not going to be my main concern here. In addition to being efficient rhetorical means, they serve to structure discourse and convey information. I propose a list of cognitive-discursive functions these formulaic phrases fulfil in discourse, and exemplify each with one or more instances of their use. The primary data include the discourse of public speaking – excerpts from Nobel Prize acceptance speeches, commencement addresses, and presidential political rhetoric (Clinton and Obama) – as well as media discourse (excerpts from an American TV series and print interviews).